Evaluation of Three Synthetic Membranes as Limiting Barrier for in vitro Drug Release Studies from Hydrogels Containing Polymeric Nanocapsules - Fontana de Andrade, Diego; Camponogara Fontana, Márcia; Carlos Ruver Beck, Ruy (Current Nanoscience, 2014)
In this work we evaluated the suitability of three synthetic membranes for the in vitro assessment of drug release from semisolid dosage forms containing polymeric nanocapsules. The use of cellulose acetate (0.45 µm pore size), polycarbonate (0.05 µm pore size) and dialysis cellulose (12 kDa cut off) membranes was investigated. For this purpose, drug release studies from hydrogels containing clobetasol propionate-loaded lipid-core nanocapsules were carried out. A higher amount of clobetasol propionate reached the release medium using cellulose acetate and polycarbonate membranes, compared to the use of dialysis cellulose membrane. Photon correlation spectroscopy analyses showed an overlap between the particle size distributions of the receptor media from the release studies using cellulose acetate and polycarbonate membranes and the original lipid-core nanocapsules suspension diluted in the receptor medium. The presence of nanoparticles was further confirmed by transmission electron microscopy. On the other hand, particle size distribution observed in the receptor medium of release studies using dialysis cellulose membrane did not show particles at nanoscale. The overall results suggest that the dialysis cellulose membrane ensures that only released drug will reach the receptor compartment, and that it should be the first choice for in vitro drug release studies from semisolid dosage forms containing drug-loaded nanocapsules.
Keywords: synthetic membranes